Menorrhagia and bleeding disorders in adolescent females - Halimeh, S. (Hämostaseologie, 2012)
In women, von Willebrand disease (VWD) is the most common inherited bleeding disorder. Since VWD and other inherited bleeding disorders are autosomal disorders, they affect women and men. Menorrhagia, or heavy menstrual bleeding (HMB), is the most common symptom of women with bleeding disorder experience. Objectively, it is defined as bleeding that lasts for more than seven days or results in the loss of more than 80 ml of blood per menstrual cycle. The prevalence of menorrhagia in a woman with a bleeding disorder ranges from 32 to 100% in patients with VWD, from 5 to 98% in patients with a platelet dysfunction and from 35 to 70% in women with a rare factor deficiency. A detailed history and a careful physical exam are the first steps towards a diagnosis in adolescents, adding a PBAC > 100 increased the sensitivity of the screening tool further to 95%. Laboratory testing should be made at the time of menstrual bleeding in an effort to capture the lowest level of VWF : Ag and FVIII : C. Treatment options for menorrhagia in VWD: antifibrinolytic therapy with tranexamic acid, (2) the non-transfusional agent desmopressin (DDAVP), (3) purified blood products that contain factor VIII and VWF concentrated from plasma and (4) hormonal preparations.
Keywords: Menorrhagia; adolescents; bleeding disorders; endometriosis; miscarriage; von Willebrand’s disease